Diversity and population-genetic properties of copy number variations and multicopy genes in cattle - Bickhart, Derek M.; Xu, Lingyang; Hutchison, Jana L.; Cole, John B.; Null, Daniel J.; Schroeder, Steven G.; Song, Jiuzhou; Garcia, Jose Fernando [UNESP]; Sonstegard, Tad S.; Van Tassell, Curtis P.; Schnabel, Robert D.; Taylor, Jeremy F.; et al. (Oxford University Press (OUP), 2016)
The diversity and population genetics of copy number variation (CNV) in domesticated animals are not well understood. In this study, we analysed 75 genomes of major taurine and indicine cattle breeds (including Angus, Brahman, Gir, Holstein, Jersey, Limousin, Nelore, and Romagnola), sequenced to 11-fold coverage to identify 1,853 non-redundant CNV regions. Supported by high validation rates in array comparative genomic hybridization (CGH) and qPCR experiments, these CNV regions accounted for 3.1% (87.5 Mb) of the cattle reference genome, representing a significant increase over previous estimates of the area of the genome that is copy number variable (∼2%). Further population genetics and evolutionary genomics analyses based on these CNVs revealed the population structures of the cattle taurine and indicine breeds and uncovered potential diversely selected CNVs near important functional genes, including AOX1, ASZ1, GAT, GLYAT, and KRTAP9-1. Additionally, 121 CNV gene regions were found to be either breed specific or differentially variable across breeds, such as RICTOR in dairy breeds and PNPLA3 in beef breeds. In contrast, clusters of the PRP and PAG genes were found to be duplicated in all sequenced animals, suggesting that subfunctionalization, neofunctionalization, or overdominance play roles in diversifying those fertility-related genes. These CNV results provide a new glimpse into the diverse selection histories of cattle breeds and a basis for correlating structural variation with complex traits in the future.
Keywords: cattle genome; copy number variation; indicine; population sequencing; taurine